2017
DOI: 10.1371/journal.pone.0176869
|View full text |Cite
|
Sign up to set email alerts
|

Flooding tolerance of four floodplain meadow species depends on age

Abstract: Numerous restoration campaigns focused on re-establishing species-rich floodplain meadows of Central Europe, whose species composition is essentially controlled by regular flooding. Climate change predictions expect strong alterations on the discharge regime of Europe’s large rivers with little-known consequences on floodplain meadow plants.In this study, we aim to determine the effects of flooding on seedlings of different ages of four typical flood meadow species. To this end, we flooded seedlings of two fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…It has been suggested that higher‐diversity communities are less negatively affected by floods and that some grasses are unaffected by floods regardless of plant diversity (Wright et al ., ). Furthermore, mature plants may tolerate flooding better than young plants (Gattringer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It has been suggested that higher‐diversity communities are less negatively affected by floods and that some grasses are unaffected by floods regardless of plant diversity (Wright et al ., ). Furthermore, mature plants may tolerate flooding better than young plants (Gattringer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…These predictors are based on various experimental studies (e.g., Gattringer et al, 2017;Gattringer, Ludewig, Harvolk-Schöning, Donath, & Otte, 2018;Van Eck, Van De Steeg, Blom, & De Kroon, 2004) or observational studies (e.g., Leyer, 2005;Mosner et al, 2015). These predictors are based on various experimental studies (e.g., Gattringer et al, 2017;Gattringer, Ludewig, Harvolk-Schöning, Donath, & Otte, 2018;Van Eck, Van De Steeg, Blom, & De Kroon, 2004) or observational studies (e.g., Leyer, 2005;Mosner et al, 2015).…”
Section: Habitat Modelmentioning
confidence: 99%
“…For each vegetation plot, we generated 81 hydrological predictors (Appendix S2). These predictors are based on various experimental studies (e.g., Gattringer et al, 2017;Gattringer, Ludewig, Harvolk-Schöning, Donath, & Otte, 2018;Van Eck, Van De Steeg, Blom, & De Kroon, 2004) or observational studies (e.g., Leyer, 2005;Mosner et al, 2015). We derived the hydrological predictors either for the entire year or only for the vegetation period, and we considered up to 6 years before the monitoring year, thus resulting in n = 14 different variations.…”
Section: Habitat Modelmentioning
confidence: 99%
See 2 more Smart Citations